The Long-Term Care Insurance System in Japan: Past, Present, and Future - Iwagami, Masao (JMA J, 2019)
The Japanese population is rapidly aging. The proportion of people aged ≥65 was 27.3% in 2016, the highest in the world. Japan achieved universal health coverage for medical care in 1961 with the introduction of the National Health Insurance (NHI) system. However, increasing expenditure on inpatient care for old people became a significant issue in society. At that time, tax-supported in-home services were mainly for old people with low incomes and little care given by family. To tackle these problems, universal health coverage for long-term care was introduced in 2000 under the Long-Term Care Insurance (LTCI) system. People aged ≥65 who satisfied the eligibility criteria and those aged 40–64 with age-related diseases are entitled to receive long-term care services at home or in facilities, irrespective of income level and availability of family caregiving. The practical benefits in kind under the LTCI system for family caregivers have been demonstrated. However, because of a recent increase in long-term care costs, especially facility-based costs, it may be necessary to give more support to family (informal) caregivers who participate in home-based long-term care. Health services research using nationwide claims data would help sustain the LTCI system through evidence-based policymaking. Recent studies have explored how to prevent deterioration of care need levels among residents of long-term care welfare facilities and how to promote a shift from facility-based to home-based long-term care services. By 2025, as the baby boomer generation is projected to reach the age of 75, the Japanese government is planning to establish a community-based integrated care system. Harmonization between long-term care and medical care, involving the informal sector and nonprofit organizations, would mitigate the increasing cost of both the NHI and LTCI systems. To achieve this, more research is warranted to understand how long-term care, medical care, and informal care can be effectively integrated in the community.